Analysis of the Independent and Sustainable Waste Recycling Center Program (PADU PADAN) from PT Pertamina EP Prabumulih Field CSR - Rosadi, Hengky; Luthfi, Muhammad; Hendra Putra, Erwin; Wahyu Tomo, Almira Chairunissa; Saddam Husen, Mohammad; Aznury, Martha; Lestari, Sari; Marieska, Marieska; Ratna Sari, Dewi; Ripandi, Irfan (Pelopor Publikasi Akademika, 2024)
The waste problem has become a disturbing problem in Prabumulih City. In Prabumulih City, there is over capacity at the Final Disposal Site. This is because the volume of waste coming in is very large and has not been managed well. The impact is very negative from an environmental, economic and social perspective. CSR PT Pertamina EP Prabumulih Field is participating in overcoming this through Program Pusat Daur Ulang Sampah Mandiri dan Berkelanjutan (PADU PADAN) as a community development (comdev) program. This research method is in the form of a qualitative field study or field research. The data collection techniques were carried out using observation with active participation, in-depth interviews, documentation and focus group discussions. The research results show: Program Pusat Daur Ulang Sampah Mandiri dan Berkelanjutan (PADU PADAN) program is an educational activity for sorting and processing organic and anorganic waste into marketable products. This program is under the auspices of the CSR of PT Pertamina EP Prabumulih Field in South Sumatra. Program Pusat Daur Ulang Sampah Mandiri dan Berkelanjutan (PADU PADAN) consists of two main programs, namely: 1) Perempuan Berdaya Bersama Kelola Sampah (MUDA BERSAMA), 2) Rumah Inovasi Daur Ulang Sampah Residu Anorganik (RINDU RESIK). The Muda Bersama Program specifically processes organic waste, while the Rindu Resik Program is a process for handling anorganic waste. These two programs have a positive impact on society both from an economic, social and environmental perspective.